Albedo decline on Greenland's Mittivakkat Gletscher in a warming climate. (12th August 2014) - Mernild, Sebastian H.; Malmros, Jeppe K.; Yde, Jacob C.; Wilson, Ryan; Knudsen, Niels T.; Hanna, Edward; Fausto, Robert S.; van As, Dirk
Abstract Albedo is one of the parameters that govern energy availability for snow and ice surface ablation, and subsequently the surface mass balance conditions of temperate glaciers and ice caps (GIC). Here, we document snow and ice albedo changes for Mittivakkat Gletscher (MG) in Southeast Greenland (2000–2013), for which an 18‐year record of direct surface mass balance measurements exists. The MODerate Imaging Spectroradiometer (MODIS MCD43A3) albedo product was used to study MG's snow and ice albedo, evaluated against supraglacial automatic weather station (AWS) observations. In general, by the end of the mass balance year (EBY), MG's AWS observed bare ice albedo reached ∼0.3 only just exceeding values observed for proglacial bedrock (∼0.2). The analysis reveals negative mean trends in the MODIS‐derived MG EBY albedo for the period 2000–2013 with a significant decline in mean glacier‐wide albedo of 0.10. The greatest decline in albedo, of 0.25, occurred near the equilibrium line altitude (ELA), an important surface cover and albedo transitional zone. The EBY albedo correlates significantly with ELA and net winter and summer glacier mass balance records.